2005
DOI: 10.1042/bj20050187
|View full text |Cite
|
Sign up to set email alerts
|

The N domain of somatic angiotensin-converting enzyme negatively regulates ectodomain shedding and catalytic activity

Abstract: sACE (somatic angiotensin-converting enzyme) consists of two homologous, N and C domains, whereas the testis isoenzyme [tACE (testis ACE)] consists of a single C domain. Both isoenzymes are shed from the cell surface by a sheddase activity, although sACE is shed much less efficiently than tACE. We hypothesize that the N domain of sACE plays a regulatory role, by occluding a recognition motif on the C domain required for ectodomain shedding and by influencing the catalytic efficiency. To test this, we construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 30 publications
4
38
0
Order By: Relevance
“…In contrast, the N-domain may lack such recognition sequences. Consistent with this is the finding that an ACE construct, composed of a tandem repeat of two ACE C-domains, is shed from cells with kinetics similar to the testis ACE protein, which contains only a single C-domain (Woodman et al, 2005). Not only was the repeated Cdomain construct shed, the sheddase enzyme cut both within the ACE stalk region and in the interdomain 8 protein bridge connecting the two C-domains.…”
Section: F Shedding Of Angiotensin-converting Enzymesupporting
confidence: 65%
See 1 more Smart Citation
“…In contrast, the N-domain may lack such recognition sequences. Consistent with this is the finding that an ACE construct, composed of a tandem repeat of two ACE C-domains, is shed from cells with kinetics similar to the testis ACE protein, which contains only a single C-domain (Woodman et al, 2005). Not only was the repeated Cdomain construct shed, the sheddase enzyme cut both within the ACE stalk region and in the interdomain 8 protein bridge connecting the two C-domains.…”
Section: F Shedding Of Angiotensin-converting Enzymesupporting
confidence: 65%
“…Limited proteolysis of ACE with endoproteinase Asp-N will cleave between the Thr615-Asp616 and the Leu1219-Asp1220 peptide bonds to generate the two catalytic domains in active form that can be separated by a lisinopril affinity column Chen et al, 2010). Several groups have suggested that in somatic ACE, the catalytic activity of the C-domain is negatively regulated by the presence of the N-domain (Binevski et al, 2003;Woodman et al, 2005).…”
Section: E Structure Of Angiotensin-converting Enzymementioning
confidence: 99%
“…2) which was eluted with 20mM Mes-NaOH (pH 6.0) and 10 µM ZnCl2 represents the 90 kDa N-domain ( fig.3; (Table 5) indicated that the catalytic efficiency (Kcat/Km) of the isolated Cdomain is about two-fold higher than that of the native sACE. These results are compatible with the notion that the catalytic activity of the C-domain is negatively regulated by it's Ndomain counterpart in native sACE (Binevski et al, 2003;Woodman et al, 2005;Skirgello et al, 2005).…”
Section: N-terminal Sequence Of the N-and C-domainssupporting
confidence: 89%
“…Although human as well as bovine sACE display negative cooperativity between the N-and Cdomains' active sites upon binding of diverse peptides or inhibitors (Binevski et al, 2003;Woodman et al, 2005;Skirgello et al, 2005), the enzymic activities are not linked to the glycosylation state. Deglycosylation of sACE from porcine lung did not markedly affect the biochemistry or structural properties of the enzyme (Baudin et al, 1997).…”
Section: N-terminal Sequence Of the N-and C-domainsmentioning
confidence: 99%
“…Work from our and other laboratories has indicated that this is most likely because there is a sheddase recognition domain in the C domain of ACE, which in somatic ACE is partly occluded by the presence of the second domain (N domain). 8,9 Indeed, when a mutant ACE was constructed in which the N domain of somatic ACE was fused directly to the stalk, this mutant was not shed, suggesting that it lacked a critical recognition element for the sheddase. …”
Section: The Transmembrane Domain (Black Coil) Spans the Lipid Bilamentioning
confidence: 99%